2022
DOI: 10.3390/foods11233918
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Household Food Processing on Pesticide Residues in Oranges (Citrus sinensis)

Abstract: In this study, the effect of various household food-processing methods (washing, peeling, processing into jam and fruit juice, freezing, storage) on pesticide residues (abamectin, buprofezin, ethoxazole, imazalil, and thiophanate-methyl) in oranges was investigated. Residue analyses were performed by quick-easy-cheap-efficient-rugged-safe (QuEChERS) extraction and liquid chromatography coupled with triple quadrupole mass spectrometry (LC-MS/MS) analysis. The limit of quantification of the method for each pesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Prior to application of a validated method into a routine analysis laboratory, method verification study should be performed to provide evidence that the validated method can be applied by the laboratory. In this context, the reliability of the method was successfully proved at our laboratory conditions and reported previously by Yolci Omeroglu et al (2022) for orange matrix. Based on the results, mean recovery (as a measure of trueness; 70-120%), precision (as repeatability and interim precision relative standard deviation-RSDr and RSDwR <20%) and LOQ of the method (0.01 mg/kg< MRL) were in accordance with the criteria set European SANTE/11312/2021 Guidance Document (SANTE, 2021).…”
Section: Methods Verification and Quality Control Studiessupporting
confidence: 72%
See 4 more Smart Citations
“…Prior to application of a validated method into a routine analysis laboratory, method verification study should be performed to provide evidence that the validated method can be applied by the laboratory. In this context, the reliability of the method was successfully proved at our laboratory conditions and reported previously by Yolci Omeroglu et al (2022) for orange matrix. Based on the results, mean recovery (as a measure of trueness; 70-120%), precision (as repeatability and interim precision relative standard deviation-RSDr and RSDwR <20%) and LOQ of the method (0.01 mg/kg< MRL) were in accordance with the criteria set European SANTE/11312/2021 Guidance Document (SANTE, 2021).…”
Section: Methods Verification and Quality Control Studiessupporting
confidence: 72%
“…Since any heat treatment process for sterilization/pasteurization of homemade juice was not included in the production step, the reduction of the pesticide residues in juice can only be attributed to deposition of the residues on the wax and cuticular section of the outer surface, which is related with their higher octanol-water partition coefficient (log Po/w). Yolci Omeroglu et al (2022) observed the same findings for orange juice. Furthermore, Tang et al (2023) stated that degradation or dissipation of five pesticides including etoxazole occurred at a rate of at least 37.6 % in sterilized citrus juice compared with the residual levels in raw citrus.…”
Section: Processing Into Lemon Juice (Lj)supporting
confidence: 71%
See 3 more Smart Citations